Angiographic Evidence of a Purely Pial Bihemispheric Intracranial Hemangiopericytoma - Nathaniel Stetson; Sudhakar Vadivelu; Jiang Y. Li; Avi Setton; David J. Chalif (Case Reports in Neurological Medicine)
Background. Classification of hemangiopericytoma (HPC) has evolved to a mesenchymal, nonmeningothelial grade two or three neoplasm according to the World Health Organization; however its blood supply has always been defined by dual origin, pial and dural contribution. Case Description. We present the case of a patient with an intracranial HPC with only pial vascular supply. Angiography confirmed the lack of dural supply to this bihemispheric intracranial mass. Subsequent histologic examination confirmed the diagnosis of hemangiopericytoma. Angiographic evidence here is atypical of the natural history of hemangiopericytomas with dual vascular supply and was critical in the decision-making towards surgical resection without tumor embolization. Conclusion. Data presented suggests the lack of dural vascular supply alone does not rule out the diagnosis of hemangiopericytoma.